2010
DOI: 10.1093/jjco/hyp187
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Trends in China

Abstract: Cancer is the leading death cause in urban China and the second one in rural China. Lung cancer is the most common cancer, followed by stomach cancer, liver cancer, esophageal cancer and colorectal cancer. Cancer Control Programs in China focus on prevention, early diagnosis and treatment. The prevention program includes an anti-smoking campaign and immunization against hepatitis B for infants and children under the age of 15. Screening for breast and cervix cancers is among efforts for the early detection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
197
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(199 citation statements)
references
References 8 publications
1
197
0
1
Order By: Relevance
“…Colorectal cancer is one of the most common malignant tumors which contribute to the fifth cause of tumor death rates in China 1, 2. The incidence of colorectal cancer is nearly 5% and the 5‐year survival rate ranges from 40% to 60% 3.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer is one of the most common malignant tumors which contribute to the fifth cause of tumor death rates in China 1, 2. The incidence of colorectal cancer is nearly 5% and the 5‐year survival rate ranges from 40% to 60% 3.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated 21,600 newly diagnosed cases of gastric cancer and 10,990 deaths would occur in the USA in 2013, although gastric cancer (3.1%) enjoyed the second largest annual declines in death rates over the past 10 years of data (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009) (Siegel et al, 2013;Society, 2013). It is reported nearly two-thirds of gastric cancer cases and deaths occur in developing countries, such as China, Korea, Central and South America and Middle East (Crew et al, 2006;Zhao et al, 2010;Jemal et al, 2011). Take China as an example, the crude gastric cancer mortality rate was 22.97 per 100,000 in urban areas and 25.58 per 100,000 in rural areas in 2004(Yang et al, 2006Jemal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In China, gastric carcinoma is the second most common cancer (Zhao et al, 2010). It is reported that almost two thirds of the cases of this type of cancer occur in developing countries and 42% in China alone.…”
Section: Introductionmentioning
confidence: 99%